Empirical and Rational Cognition of the Education Reality in Lithuania in the First Half of the XX Century - Montvilaitė, Sigita (Acta Paedagogica Vilnensia, 2005)
The first educational science works characteristic of theoretical and empirical research appeared in Lithuania in the first half of the XX century. Although the researches were not many, they show that there were educators who searched for ways of better knowing the child's mind not only from books but also through using various research techniques. Data of the first researches arising from the practical school work and intended for its improvement are attributed to the everyday cognition. Upon appearance of the scientific research base and a certain scientific community, an empirical research of reality is fixated, and it is able to describe reality by mathematical means. Nevertheless, there is one goal to be achieved through every day and scientific cognition, i.e. to know the educational reality and to find truth. Influence of different philosophical trends reflected in the field of applying research methods – from the most abstract theoretical thinking to the application of observation, interview and experiment methods. The research showed that Lithuanian educators of the first half of the XX century tried to kccp to the fundamental principles of the scientific concept of modern education formulated by l. Kant. Empirical and rational cognition of the educational reality, like two inseparable complementary processes of an undivided scientific research, was characteristic of the Lithuanian educational science in the first half of the XX century.
Keywords: history of education science; education; empirical and rational cognition; research methods; educational reality